PERTIMBANGAN HAKIM DALAM TINDAK PIDANA PENGANIAYAAN DIRENCANAKAN YANG MENGAKIBATKAN LUKA BERAT - Muhammad Fadhiil Yashendra; Ermania widjajanti (Faculty of Law, Universitas Trisakti, 2023)
In case number 94/Pid.B/2021/PN. Prn, the defendant severely abused the victim by swinging a machete and striking her in the neck once and in the back twice. As a result, the witness Rabadi was injured and bleeding, and the victim was unable to perform any tasks. The formulation of the issue is how the judge weighs various factors when rendering a decision regarding those who commit the crime of persecution intended by Article 351 paragraph (2) of the Criminal Code (Decision No. 94/Pid.B/2021/PN Prn) and whether the perpetrator's actions are in compliance with that provision. The research methodology makes use of secondary data, normative research designs, and analytical descriptive research. According to the findings of the study and discussion, the defendant was established to have committed significant abuse, which was supported by the witness's statement and intention as well as the Visum Et Repertum letter. The defendant planned her acts, as there was a deadline and he had to prepare everything. Conclusion: The defendant's actions satisfied Article 351 paragraph (2) of the Criminal Code, but they were improper in relation to that fulfillment because Article 353 paragraph (2): Criminal Code included a planning element, specifically serious maltreatment with a plan.